Investigating Teacher Voice Through Blogs: Policy, Practice, and Local Knowledge - Greene, Kiersten (AoIR Selected Papers of Internet Research, 2013)
Teachers, especially those working in high-poverty, urban school districts, are given little if any voice in contemporary policy formation. Prevailing policies often ignore teachers’ professional experience, and instead place heavy constraints on teachers’ classroom practice, squelch professional decision-making, and limit the possibility of effectively implementing pedagogies aimed at ensuring the success of all students. Educational historians posit that the absence of teachers’ voice in the policymaking process is largely due to the traditional isolation in teaching. This paper asserts that blogs written by teachers offer a way to share expertise and local knowledge with policymakers. The main objectives of this paper are to 1) offer an alternative to the enduring, counterintuitive practice of educational policymaking, and 2) explore blogs written by teachers as a way to “see” into the classroom.